Cambodia : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cambodia. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights growth in the Cambodian economy of about 7 percent in 2015, supported by strong garment exports, real estate and construction activity, and a reduction in oil prices. Inflation unexpectedly picked up at the end of 2015, to 2.8 percent, owing to higher food prices following extreme weather, but it remains well contained. Private sector credit growth has averaged nearly 30 percent over the past three years, doubling the credit-to-GDP ratio to 62 percent by the end of 2015. The near-term outlook remains broadly favorable. Growth is projected to remain robust at about 7 percent for 2016-17, supported by strong garment exports and real estate and construction activity.